1992
DOI: 10.1044/0161-1461.2302.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialect on the Determination of Speech-Reception Thresholds in Spanish-Speaking Children

Abstract: Word lists spoken in Castillian, Caribbean, and Mexican dialects were compared as stimuli for the determination of speech-reception thresholds (SRT) in 12 6- to 7-year-old Spanish-speaking, Puerto Rican children, using a balanced, crossover design. No statistically significant differences were found among dialects. All subjects had SRTs that were 2 dB lower than ( p <0.01), but highly correlated with, their pure-tone averages ( r s >0.85). The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although the overall psychometric slope values are similar between the two dialects, it would be of interest to conduct a direct examination of how speakers of Puťo nghuà (mainland China) would perform on these Taiwan Mandarin word recognition materials and vice versa. To date, there has been limited research on how a regional dialect might affect word recognition testing (Schneider, 1992;Weisleder & Hodgson, 1989). In the study by Weisleder and Hodgson, findings indicated that a regional dialect can affect the validity of word recognition testing in Spanish; however, Schneider found the effects of regional dialect to not significantly affect the speech recognition scores of Spanish-speaking children.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall psychometric slope values are similar between the two dialects, it would be of interest to conduct a direct examination of how speakers of Puťo nghuà (mainland China) would perform on these Taiwan Mandarin word recognition materials and vice versa. To date, there has been limited research on how a regional dialect might affect word recognition testing (Schneider, 1992;Weisleder & Hodgson, 1989). In the study by Weisleder and Hodgson, findings indicated that a regional dialect can affect the validity of word recognition testing in Spanish; however, Schneider found the effects of regional dialect to not significantly affect the speech recognition scores of Spanish-speaking children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schneider (1992) found that the differences in results were not clinically signifi cant when Puerto Rican Spanish-speaking children ' s SRTs were measured with word lists using Castilian, Caribbean, and Mexican dialects. Likewise, Nissen et al (2013) also found that the differences in SRTs and word recognition scores were not clinically signifi cant when Mainland Mandarin and Taiwanese Mandarin speaking adults with normal hearing were tested with materials from two different Mandarin dialects.…”
mentioning
confidence: 96%